Glutathione peroxidase 4 as an emerging therapeutic target in osteoarthritis: focus on ferroptosis - Zhang, Lin; Li, Jinglin; Yang, Xuxu; Yang, Lidan (Frontiers in Cell and Developmental Biology, 2026)
Osteoarthritis (OA) is a degenerative joint disease characterized by articular cartilage degradation, extracellular matrix breakdown, low-grade chronic inflammation, and pain. Its etiology is complex and treatment options are limited. In recent years, ferroptosis, a regulated form of cell death driven by iron-dependent lipid peroxidation, has gained significant attention in OA pathogenesis. Glutathione peroxidase 4(GPX4), serves as the central enzyme that halts lipid peroxidation and inhibits ferroptosis. Its expression and activity are altered in OA cartilage under pathological conditions, suggesting a crucial role for GPX4 in OA pathogenesis and treatment. This review summarizes the molecular characteristics and antioxidant functions of GPX4, evaluates experimental evidence linking GPX4 and ferroptosis in OA, outlines upstream and downstream molecular mechanisms regulating GPX4, and summarizes therapeutic strategies targeting GPX4, including pharmacological, gene, and combination therapies. It also discusses current research challenges and future directions. Finally, key pathways and strategic recommendations for translating GPX4 and ferroptosis research into clinical OA treatments are proposed.